Writings on the Wall: Empowering Travel Blog Hers in Malaysia - Senutha, P.R.; Nor Hafizah, S. (IDOSI Publications, 2017)
Blogs or writings on the virtual wall are observed as a technology that uses a cost-free writing space to convey ones words and experiences with no specified skills. Experiences are built by matching the effect of traveler’s culture and language, values and beliefs. Travel blog writings are narratives that provide a rich source of knowledge about the traveler’s significance find through travelling, revealing the impression of travel in their life. This paper explores the growing female travel bloggers in Malaysia with strong self -sense of confidence and assertive voice while they develop a deep sense of positively impacting their reader’s knowledge and decision-making. Apart from just being a regular traveler, these women take it a step further by sharing, informing and helping others to make travel decisions through their blogs. The travel blogs become a representation of female liberation and empowerment in the world of travel and technology which is mainly structured by men. The blog descriptions, narratives, comments and posted images owned by ten Malaysian female travelers substantiates that travel blogs extend a strong sense of empowerment among the bloggers by building their sense of control and efficacy while understanding and relating to their social community. Women, in this case Malaysian females are becoming more liberated as technologies such as blogs become their outlet for voices and choices to be heard. The empowered blog authors go beyond just being a female who travels and choose to inspire others through their writings on the virtual world.